PERBANDINGAN NILAI KEKUATAN TARIK KOMPOSIT MENGGUNAKAN METODE HAND LAY UP DAN METODE VARI - Utami, Lega Putri; Ginting, Delovita; Nasution, Ahmad Kafrawi; Istana, Budi (Sistem Informasi, 2019)
Some Types of the method of making composite materials are the Vacuum Assited Resin Infusion (VARI) Method and the Hand Lay Up Method. The purpose of this study was to compare the tensile strength of composite materials made using the hand lay up and VARI methods. The types of fibers used as composite materials are palm frond fibers and matrices used in polyester resin. Composites reinforced with palm fronds are printed using the hand lay up and VARI methods. The results showed the value of composite tensile strength with the hand lay up method of 27.37 MPa and composite tensile strength using the VARI method of 28.40 MPa. From the results of the study, the differences in the tensile strength values of the two methods were obtained.